The effect of a changing fuel solution composition on a transient in a fissile solution. (August 2016) - Major, M.; Cooling, C.M.; Eaton, M.D.
Abstract: This paper presents an extension to a point kinetics model of fissile solution undergoing a transient through the development and addition of correlations which describe neutronics and thermal parameters and physical models. These correlations allow relevant parameters to be modelled as a function of time as the composition of the solution changes over time due to the addition of material and the evaporation of water from the surface of the solution. This allows the simulation of two scenarios. In the first scenario a critical system eventually becomes subcritical through under-moderation as its water content evaporates. In the second scenario an under-moderated system becomes critical as water is added before becoming subcritical as it becomes over-moderated. The models and correlations used in this paper are relatively idealised and are limited to a particular geometry and fissile solution composition. However, the results produced appear physically plausible and demonstrate that simulation of these processes are important to the long term development of transients in fissile solutions and provide a qualitative indication of the types of behaviour that may result in such situations. Highlights: A point kinetics model of a fissile solution is constructed. Major processes affecting solution composition are included. Correlations for neutronics parameters as a function of composition are derived. Two simulations are run where the effect of changing composition is important. The effects on results of the evaporation and addition of water are discussed.